2020
DOI: 10.3390/nano10122445
|View full text |Cite
|
Sign up to set email alerts
|

Metal Exsolution to Enhance the Catalytic Activity of Electrodes in Solid Oxide Fuel Cells

Abstract: Exsolution is a novel technology for attaching metal catalyst particles onto ceramic anodes in the solid oxide fuel cells (SOFCs). The exsolved metal particles in the anode exhibit unique properties for reaction and have demonstrated remarkable stabilities under conditions that normally lead to coking. Despite extensive investigations, the underlying principles behind exsolution are still under investigation. In this review, the present status of exsolution materials for SOFC applications is reported, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 131 publications
0
38
0
Order By: Relevance
“…While it has been known for some time that interactions between a group 10 transition-metal catalyst and a perovskite oxide support, including exsolution phenomena in which the metal can ingress into the oxide under oxidizing conditions and egress under reducing conditions, can affect the structure and dispersion of the metal, 30 the results obtained here demonstrate that these interactions are quite complex and can impart unique catalytic properties beyond simply affecting the metal dispersion. Furthermore, these interactions are highly dependent on both the perovskite composition and the identity of the catalytic metal, making it difficult to generalize how the perovskite will affect activity for any particular reaction.…”
Section: ■ Discussionmentioning
confidence: 77%
“…While it has been known for some time that interactions between a group 10 transition-metal catalyst and a perovskite oxide support, including exsolution phenomena in which the metal can ingress into the oxide under oxidizing conditions and egress under reducing conditions, can affect the structure and dispersion of the metal, 30 the results obtained here demonstrate that these interactions are quite complex and can impart unique catalytic properties beyond simply affecting the metal dispersion. Furthermore, these interactions are highly dependent on both the perovskite composition and the identity of the catalytic metal, making it difficult to generalize how the perovskite will affect activity for any particular reaction.…”
Section: ■ Discussionmentioning
confidence: 77%
“…This time-and cost-effective method has been successfully utilized to form various transition metal nanoparticles, including noble metals [7][8][9] and first-row transition metals. [10][11][12] Monometallic nanoparticles exsolved on the host materials have been extensively applied in various chemical and energy conversion processes. [13][14][15] The finely dispersed nanoparticles possess excellent catalytic activities and most importantly, their unique anchored structure on host materials was reported to improve their stability significantly under harsh conditions.However, the exsolution of transition metal cations with mixed-valence has been rarely reported because of their low reducibility and high segregation energy.…”
mentioning
confidence: 99%
“…Lastly, recent studies have reported that not only improving the thermal/chemical stability of the electrode itself but also introducing a robust metal-oxide composite nanocatalyst onto a complex SOFC electrode can effectively realize highperformance SOFC electrodes. 10,66,67 Metal nanocatalysts are applied in various research elds due to their superior catalytic activity. 68 However, their thermal/chemical instability at a high temperature limits their application in devices operated at high temperatures.…”
Section: Studies Of the Thermal/chemical Stabilization Of Electrodesmentioning
confidence: 99%
“…Ex-solution, a nanocatalyst fabrication technology that involves spontaneous phase transformation on the oxide surface under a reducing heat treatment, has been in the spotlight lately in the eld of heterogeneous catalysis. 66,67,88,89 The unique property of an ex-solved nanocatalyst is that ex-solved particles are strongly anchored on the support, resulting in high durability at high temperatures compared to nanoparticles prepared by conventional inltration. Accordingly, this method has brought remarkable progress in the eld of SOFCs as well as chemical catalysts.…”
Section: Studies To Facilitate the Self-assembly Of Nanocatalystsmentioning
confidence: 99%